Effect of manual lymphatic drainage on upper limb lymphedema after surgery for breast cancer - Chmelová, Kristína; Nováčková, Marta (Ceska gynekologie, 2022)
OBJECTIVE: Evaluation of the effect of manual lymphatic drainage on lymphedema of the upper limb after previous axillary lymphadenectomy/sentinel node bio-psy during the maintenance phase of lymphedema after the breast cancer surgery. MATERIAL AND METHODS: A total of 30 patients after surgical treatment of unilateral breast cancer underwent 10 manual lymphatic drainages within 8 consecutive weeks. All patients underwent upper limb circumference measurements before and after the study and completed two specialized EORTC questionnaires (QLQ-C30 and QLQ-BR23). RESULTS: The average time between surgery and admission into this study was 32.5 months. In the beginning of the study, lymphedema was present for an average of 19.8 months. At the end of a series of manual lymphatic drainages, the average volume decrease of the limb with lymphedema was 3% (1.5-5.6%). In contrary, the average loss of volume on the healthy (control) upper limb was only 0.4%. The average reduction of lymphedema volume after therapy achieved 57% (37-88%). After a series of manual lymphatic drainages, the results of the EORTC QLQ-C30 questionnaire showed a statistically significant improvement in physical and role functions, fatigue, nausea and vomiting, pain, dyspnea and constipation, while the results of the EORTC QLQ-BR23 questionnaire showed a statistically significant improvement in the arm and breast symptoms. There was no statistically significant deterioration in any of the monitored parameters. CONCLUSION: The results of the study showed a positive effect of manual lymphatic drainage on the maintenance phase of lymphedema in patients after breast cancer surgery. The questionnaires showed a significant improvement in hand and arm symptoms as well as an improvement of the other functions and symptoms affecting quality of life. Further studies should be performed on groups of patients with the maintenance phase of upper limb lymphedema to confirm or disprove our results.
Keywords: Lymphedema; Manual Lymphatic Drainage; nádory prsu; kvalita života; manual lymphatic drainage; lidé; horní končetina; Female; axillary lymphadenectomy; Breast Neoplasms; Upper Extremity; Quality of Life; lymphedema; breast cancer; ženské pohlaví; lymfedém; manuální lymfatická drenáž; Humans